Requirement of Intravenous Fluid and Insulin in the Management of Diabetic Ketoacidosis to Overcome the Crisis: Experience in a Specialized Hospital (Journal of Medicine, 2017)
Background: Among the acute metabolic decompensation states of diabetes mellitus, diabetic ketoacidosis (DKA) is relatively common. It commonly occurs in diabetic patients who have given up taking insulin or who have got some sort of infection. Treatment consisted of correction of dehydration, hyperglycaemia, electrolyte imbalance, acidosis and antibiotics for the patients who have some sort of infection or treatment of other precipitating cause, if present.Methods: This cross sectional study was performed in BIRDEM Hospital in 2012 on fifty adult diabetic ketoacidosis patients who fulfilled inclusion and exclusion criteria to find out the total amount of intravenous fluid (normal saline) needed to treat diabetic ketoacidosis.Results: DKA occurred more in previously diagnosed (60%) diabetic patients and frequency was more in poor, village people and there was no significant sex differences. Along with polyuria (24%) and polydipsia (16%), nausea (32%), vomiting (48%), abdominal pain (28%) and feature of infection were common. Infection (38%) and omission of insulin doses (34%) were the main cause. The glycaemic status was poor in most cases. Most patients had mild (32%) to moderate (60%) acidosis and gross electrolyte disturbance was not that much common. Leukocytosis (88%) was invariably present, even without any infection. Outcome (90% survival) was comparable with developing world. In management of DKA 40% patients required 11 liters of fluid, who had increased diuresis. 24% patients required 91-100 units of insulin, and most (32%) patients took 48 hours for correction of acidosisConclusions: Diagnosis and treatment of diabetic ketoacidosis is not difficult if recognized early. Adequate fluid replacement is important to prevent the mortality.J MEDICINE Jan 2018; 19 (1) : 18-21